Sex Positive Social Work Education: Integrating Content into HBSE Courses and Beyond. Issue 1 (1st January 2020) - Dodd, SJ; Katz, Colleen Cary
ABSTRACT: Sexuality is an integral part of human behavior throughout the lifespan, with sexual health and well-being having an important impact on overall health and well-being, including increased life satisfaction and improved quality of relationships. As such, social workers encounter issues related to sexuality in all aspects of practice. However, very limited content on sexuality, especially positive sexuality, is included in the social work core curriculum. The purpose of this paper is to highlight the need for and ways in which a sex positive, strengths-based approach to sexuality can be anchored within the Human Behavior and the Social Environment (HBSE) core courses. A model for integration is provided.